Atypical temperature-dependence of symmetry transformation observed in a uranyl phosphonate. Issue 22 (17th May 2016) - Zheng, Tao; Gao, Yang; Gui, Daxiang; Chen, Lanhua; Sheng, Daopeng; Diwu, Juan; Chai, Zhifang; Albrecht-Schmitt, Thomas E.; Wang, Shuao
Abstract : The first example of phase transformation from a centrosymmetric space group at LT to a chiral space group at HT is reported, which was clearly resolved in a single-crystal-to-single-crystal manner in a 3D uranyl(vi ) phosphonate compound. Abstract : The example of phase transformation from a centrosymmetric space group at low temperature (LT) to a chiral space group at high temperature (HT) is reported, which was clearly resolved in a single-crystal-to-single-crystal manner in a 3D uranyl(vi ) phosphonate compound [TMA][(UO2 )2 (1, 3-pbpH)(1, 3-pbpH2 )] (1 ) (TMA + = tetramethylammonium cation; 1, 3-pbpH4 = 1, 3-phenylenebis(phosphonic acid)).